Association of high sensitivity C-reactive protein-triglyceride glucose index and chronic kidney disease: a cross-sectional study - Zhang, Fengxu; Wang, Zhengfang; Zhang, Han (Frontiers in Endocrinology, 2026)
BackgroundChronic kidney disease (CKD) represents a significant global health burden. Its pathogenesis is closely linked to a state of metabolic inflammation, involving insulin resistance and chronic low-grade inflammation. The high-sensitivity C-reactive protein-triglyceride glucose index (CTI) is a novel composite biomarker integrating inflammatory and metabolic information, yet its association with CKD in the general population remains unclear.ObjectiveThis study aimed to investigate the cross-sectional association between the CTI and the prevalence of CKD in a health examination population.MethodsA total of 10–287 adults who underwent routine health check-ups were included. The CTI was calculated as the product of high-sensitivity C-reactive protein (hs-CRP) and the triglyceride-glucose (TyG) index. CKD was defined as an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m². Logistic regression models were used to assess the association of CTI (as a continuous variable and in quartiles) with CKD. Diagnostic performance was evaluated using the area under the receiver operating characteristic curve (AUC). The shape of the association and its heterogeneity were explored using restricted cubic splines and subgroup analyses.ResultsA total of 163 (1.58%) participants were identified as CKD. After full adjustment for confounders, each unit increase in CTI was associated with a 2.25-fold increased odds of CKD (OR = 2.25, 95%CI: 1.66–3.06). Compared to participants in the lowest CTI quartile, those in the highest quartile had a 2.17-fold higher risk of CKD (OR = 2.17, 95% CI: 1.25–3.76; P for trend = 0.001). A nonlinear dose-response relationship was observed between CTI and CKD (P for nonlinearity = 0.012). The CTI demonstrated superior diagnostic performance for CKD (AUC = 0.69, 95% CI: 0.64–0.73) compared to its individual components, the TyG index (AUC = 0.66) and hs-CRP (AUC = 0.59). Subgroup analyses revealed that the association was particularly pronounced in males, individuals aged <60 years, and those with a history of alcohol consumption.ConclusionIn a health examination population, a higher CTI level was independently and nonlinearly associated with an increased prevalence of CKD, and it showed better diagnostic performance than individual inflammatory or metabolic markers alone. The CTI may serve as a useful tool for identifying individuals at high risk for CKD, especially for early risk stratification in specific subgroups.